Research of compression strength of fissured rock mass - A. G. Protosenya; P. E. Verbilo (Zapiski Gornogo instituta (1999), 2017)
The article examines a method of forecasting strength properties and their scale effect in fissured rock mass using computational modelling with final elements method in ABAQUS software. It shows advantages of this approach for solving tasks of determining mechanical properties of fissured rock mass, main stages of creating computational geomechanic model of rock mass and conducting a numerical experiment. The article presents connections between deformation during loading of numerical model, inclination angle of main fracture system from uniaxial and biaxial compression strength value, size of the sample of fissured rock mass and biaxial compression strength value under conditions of apatite-nepheline rock deposit at Plateau Rasvumchorr OAO «Apatit» in Kirovsky region of Murmanskaya oblast. We have conducted computational modelling of rock mass blocks testing in discontinuities based on real experiment using non-linear shear strength criterion of Barton – Bandis and compared results of computational experiments with data from field studies and laboratory tests. The calculation results have a high-quality match to laboratory results when testing fissured rock mass samples.